Design of Control Information System Web-Based 5R Action Plan (Case Study: PT. Bimasakti Karya Prima) - Padeli, Padeli; Oktaviani, Miatri; Latifah, Della Nur (Pandawan, 2020)
Abstract The 5R Action Plan is a method for organizing, managing, and scheduling activities as a whole. To help do this, we need an application that is able to help the company control the workplace conditions. PT Bimasakti Karyaprima intends to update the 5R repair control system application more specifically in the action plan application, where they were previously still computerized to become a computerized application because the reasons for the old system of the 5R Action Plan activities can only be done by certain parties financing and scheduling that have not been certainly. a long time to send information. This study aims to analyze the problems that occur and then propose a system design at PT Bimasakti Karyaprima. Researchers collect data by observing, interviewing, and studying literature. The analytical method used by researchers is the PIECES analysis. Researchers use the Unified Modeling Language (UML) as a tool for creating model designs and system designs. The results of this study are a repair control application system that is created using the Codeigniter framework with PHP as the programming language and MySQL as the database. Finally, researchers use (QA) Quality Asurance Testing to test the functionality of the application system that researchers created. Keywords: 5R action plan, Cost, Control Applicationd